Graphene Oxide-Based Q-Switched Erbium-Doped Fiber Laser - Yap, Y.K.; Huang, N.M.; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Physics, 2013)
We demonstrate a pulsed ring erbium-doped fiber laser based on graphene oxide (GO), employing a simplified Hummer's method to synthesize the GO via chemical oxidation of graphite flakes at room temperature. By dipping a fiber ferrule end face onto the GO suspension, GO is successfully coated onto the end face, making it a simple saturable absorption device. A stable Q-switched pulsed fiber laser is achieved with a low pump threshold of 9.5 mW at 980 nm. The pulse repetition rate ranges from 16.0 to 57.0 kHz. The pulse width and the pulse energy are studied and discussed.